Peningkatan Kesadaran Hukum Masyarakat Pesisir Terhadap Perlindungan Hak Atas Kesehatan Perempuan dan Anak Melalui Penyuluhan Hukum di Desa Mowundo, Kabupaten Konawe Utara - Dewi Ratnasari Rustam; Sabrina Hidayat; Ramadan Kiro (Jurnal Ilmu Sosial dan Humaniora, 2026)
Coastal communities possess social, economic, and geographic characteristics that can create barriers to the fulfillment of the right to health, particularly for women and children. Limited access to legal information and healthcare services means that some community members do not fully understand that health is a fundamental right guaranteed by the constitution and statutory regulations. This community service initiative aims to raise legal awareness among coastal residents in Mowundo Village, North Konawe Regency, regarding the protection and fulfillment of the right to health for women and children. The activity was conducted using a legal outreach method comprising preparation, material presentation, interactive discussion, a question-and-answer session, and an evaluation of participant understanding. The outreach material covered the legal basis for the right to health, women's rights regarding reproductive health services, children's rights to adequate healthcare and proper growth and development, the prevention of violence against women and children, and mechanisms for lodging complaints and resolving rights violations. The results indicate an improved understanding among the community regarding the status of women and children as rights-holders, as well as the responsibilities of families, the community, village government, and the state in ensuring the fulfillment of the right to health. The initiative also encouraged residents to be more proactive in accessing healthcare services, filing complaints, and participating in creating a healthy coastal environment that is supportive of women and children. Thus, legal outreach serves as an educational tool to strengthen legal awareness and support the sustainable improvement of public health standards.